PENGEMBANGAN CMS TODOYU SEBAGAI CMS MANAJEMEN PROYEK VERSI INDONESIA - Shomad, Abdush; susilo, dahlan; retnoningsih, dwi (Gaung Informatika, 2014)
Todoyu is a web based system for project management, time tracking, and billing agencies specifically tailored to the needs of small-medium sized services such as lawyers, engineers and architects, services, advertising and PR agencies. Todoyu improve billing accuracy and timeliness, saving companies time and money, and remove the risk of the billing process. The final task is to develop the CMS Todoyu Todoyu CMS Version 2.3 Indonesia. The achievement of this final project is described as follows: (1) The development of the final project successfully added language option Indonesia the Local Package. (2) The development of the final project is successfully making Todoyu responsive CMS display when accessed from mobile devices. (3) Based on the results of testing the system on this final can be concluded that the development of this project is based on the F test with 0,025 siknifikansi meningkatkat WebQual total assessment score, while the T test based on variable Usability improved quality.